Anaerobic digestion of brewer’s spent grain with biochars—biomethane production and digestate quality effects - Świechowski, Kacper; Rasaq, Waheed A.; Syguła, Ewa (Frontiers in Energy Research, 2023)
In this research, biochar (BC) made from the brewer’s spent grain at temperatures of 300, 450, and 600 °C was produced and subjected to the anaerobic digestion of the brewer’s spent grain. BC shares of 2, 5, 10, and 50% concerning total solids of the substrate were tested at three substrate-to-inoculum ratios of 0.5, 1.0, and 2.0, respectively. The anaerobic digestion process was performed at 37 °C and took 30 days. For anaerobic digestion, biomethane production was recorded and used for kinetics parameter determination according to the first-order model. After the process, process residues (digestate) were analyzed for fertilizing potential. The biomethane yield differs from 264 to 325 mL×gvs−1, while kinetics parameters were 292.7–344.7 mL×gvs−1, 0.08–0.11 d−1, and 24–42.5 mL×(gvs×d)−1, for ymax, k, and r, respectively. The main factors affecting biomethane production were substrate-to-inoculum ratio and BC share. No specific effect between BC types on biomethane yield was found. An increase in BC share from 2% to 50% concerning specific SIR results in biomethane production improvement in the range of 1.8% to 10%. The main factors affecting the quality of digestate (nutrients) were the quality of the used inoculum and the quantity of the used substrate. The research results were complex and showed that the final effect of BC supplementation depends not only on BC properties, but also on process operational parameters and the quality of the used feedstock.